Mandela in/and Poetry (Altre Modernità, 2014)
In 1994, in his first speech to the parliament of South Africa, Nelson Mandela quoted the Afrikaner poet Ingrid Jonker and read The child who was shot dead by soldiers at Nyanga. This unorthodox choice was in fact politically fine-tuned and had an emotional impact both on the new-born Rainbow Nation and on Mandela’s stature as a 20th century-icon. A passionate reader of poetry, Mandela is one of the contemporary figures to whom the highest number of lines has ever been dedicated. Poets have celebrated him in in the forms of elegy, song, ballad, epistle, epic, ode, tribute, sonnet, rap, dub poetry, haiku and so forth. Poets started fashioning his public persona as early as the mid-Sixties when, banned and sentenced to life imprisonment, he became the world’s most famous invisible prisoner. Transformed into metaphors, blended with virtues, identified with private and collective historical events, associated with specific spaces, Mandela is above all identified with the prison where he spent eighteen years: Robben Island. In poetry, the osmotic intercourse between Mandela and Robben Island is a persistent topic with a strong symbolic function as the island catalyses issues which makes it a synecdoche of South Africa itself: a segregated place where brutality and injustice ruled but also a laboratory where resistance and hope developed. This article will examine a series of poems on Mandela and Robben Island starting from Dennis Brutus’ compositions on the subject, the first of which dates from 1963, up to post-apartheid lyrics.
Keywords: South African poetry; Nelson Mandela; Robben Island; Dennis Brutus; prison writing; apartheid